Assessing the Parenting Stress Index-Short Form (PSI-SF) for Latinx Parents of Children with Intellectual and Developmental Disabilities Within Exploratory Structural Equation Modeling and Structural Equation Modeling-Based Generalizability Theory Frameworks - Hyeri Hong; Kristina Rios (Psychiatry International)
Although the Parenting Stress Index-Short Form (PSI-SF) is widely applicable, there has been a dearth of research on the psychometric properties and item wording effects associated with the cultural sensitivity of the instrument. This study investigated the psychometric properties, the factor structure, and the negative and positive item wording effects of PSI-SF for 96 Latinx parents of children with intellectual and developmental disabilities in the United States within exploratory structural equation modeling, and structural equation modeling-based generalizability theory frameworks. This study produces the following noteworthy findings. First, the ESEM bifactor model with negatively and positively phrased items best captured the theoretical frameworks underlying the structure of the PSI-SF. Second, adding method factors enhanced the model fits of all the factor models. Third, this study discovered several items with great proportions of method factors. This study recommended that the items with high proportions of method factors, which may likely be culturally insensitive to Latinx parents, be examined further and refined. With the use of accurately assessed PSI-SF scores, practitioners will be better able to support and empower Latinx parents of children with IDD and better meet their needs through the FIRME program, a parent advocacy initiative.